Evaluation of as deposit HVOF coating for corrosion and sliding wear resistance. (2022) - Chourasia, Shubhangi; Dhankhar, Tushar; Shahid, Mohd; Lal Meena, Shanti; Sharma, Pulkit; Tyagi, Ankit
Abstract: The entire world faces pollution allied problems due to the emission of harmful gases and pollution enabled manufacturing processes at various levels. That's why the demand for cost-effective and less polluting coatings is in colossal need to decrease carbon footprints, reduce pollution, save energy, and reduce friction among the mating parts. In the present work, the carbon mixed composite coatings were by using HVOF technology. The developed coating surface morphology was studied using SEM, EDS, corrosion tester, and pin on disc tribometer at high temperature. The tribological behaviour of developed coatings was tested and following results were obtained, value of COF changes from 0.15 to 0.58 during the experiment. In contrast, wear results varies from 55 to 140 µm in the considered tested condition. The coated and uncoated samples were dipped in solution for 6 h to study the corrosion behaviour of developed coating, where the candidate recorded, 0.22–0.06 g decrement in mass loss, when sample was dipped for 6 h due to the presence of protective coatings onto the sample of substrates. The experimental results shows decrease in mass loss about 72.7% at the time of corrosion test, while 74.13% and 60.7% of the decrease in COF and wear respectively at tested condition.